Physicochemical Stability of Extemporaneously Prepared Oral Suspension of Fluconazole 50 mg/mL in SuspendIt™ - Ip Kendice; Shan Ashley; Carvalho Maria; Baker Stacey; Banov Daniel (De Gruyter, 2018)
There is a lack of an age-appropriate formulation of fluconazole. The extemporaneous preparation of an oral suspension with an extended beyond-use-date may represent a good therapeutic alternative for the paediatric population.